2021
DOI: 10.3390/vaccines9091038
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Conserved Chimeric Vaccine for Induction of Strong Immune Response against Staphylococcus aureus Using Immunoinformatics Approaches

Abstract: Staphylococcus aureus is one of the most notorious Gram-positive bacteria with a very high mortality rate. The WHO has listed S. aureus as one of the ESKAPE pathogens requiring urgent research and development efforts to fight against it. Yet there is a major layback in the advancement of effective vaccines against this multidrug-resistant pathogen. SdrD and SdrE proteins are attractive immunogen candidates as they are conserved among all the strains and contribute specifically to bacterial adherence to the hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…There are a total of 24 pairs of residues that can be exploited for disulfide engineering, according to the findings (Supplementary Table 6). However, after considering additional factors such as energy and χ 3 value, only two pairs of residues were chosen because their values fall within the acceptable range, i.e., energy must be less than 2.2 and Chi3 must be between − 87 and + 97° [ 32 ]. As a result, two mutations were generated on the residue pairs ALA9-ALA232, and VAL210-GLY246 with a χ 3 angle of − 86.78° and energy of 1.91 kcal/mol, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…There are a total of 24 pairs of residues that can be exploited for disulfide engineering, according to the findings (Supplementary Table 6). However, after considering additional factors such as energy and χ 3 value, only two pairs of residues were chosen because their values fall within the acceptable range, i.e., energy must be less than 2.2 and Chi3 must be between − 87 and + 97° [ 32 ]. As a result, two mutations were generated on the residue pairs ALA9-ALA232, and VAL210-GLY246 with a χ 3 angle of − 86.78° and energy of 1.91 kcal/mol, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Vaccination is a widely employed technique for improving the host immune mechanism against a specific pathogen [ 40 , 41 ]. Producing a range of vaccines, such as live or attenuated vaccines, is expensive, time-consuming, and takes a long time to reach the market [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…During immune simulation, we observed that the level of B-cells and T-cells increases with every injection and maintains their population level. Furthermore, a higher level of macrophages, dendritic cells, and cytokines makes vaccine constructs capable of establishing an antibacterial environment [ 66 , 67 ]. The simulation analysis of the immune response produced by our designed vaccine confirmed that it would induce a proper immune response after exposure.…”
Section: Discussionmentioning
confidence: 99%